PET Imaging of Serotonin Transporters with 4-[18F]-ADAM in a Parkinsonian Rat Model with Porcine Neural Xenografts. Issue 2 (February 2016) - Chiu, Chuang-Hsin; Li, I-Hsun; Weng, Shao-Ju; Huang, Yuahn-Sieh; Wu, Shinn-Chih; Chou, Ta-Kai; Huang, Wen-Sheng; Liao, Mei-Hsiu; Shiue, Chyng-Yann; Cheng, Cheng-Yi; Ma, Kuo-Hsing
Parkinson's disease (PD) is a neurodegenerative disease characterized by a loss of dopaminergic neurons in the nigrostriatal pathway. Apart from effective strategies to halt the underlying neuronal degeneration, cell replacement now offers novel prospects for PD therapy. Porcine embryonic neural tissue has been considered an alternative source to human fetal grafts in neurodegenerative disorders because its use avoids major practical and ethical issues. This study was undertaken to evaluate the effects of embryonic day 27 (E27) porcine mesencephalic tissue transplantation in a PD rat model using animal positron emission tomography (PET) coupled with 4-[ 18 F]-ADAM, a serotonin transporter (SERT) imaging agent. The parkinsonian rat was induced by injecting 6-hydroxydopamine into the medial forebrain bundle (MFB) of the right nigrostriatal pathway. The apomorphine-induced rotation behavioral test and 4-[ 18 F]-ADAM/animal PET scanning were carried out following 6-OHDA lesioning. At the second week following 6-OHDA lesioning, the parkinsonian rat rotates substantially on apomorphine-induced contralateral turning. In addition, the mean striatal-specific uptake ratio (SUR) of 4-[ 18 F]-ADAM decreased by 44%. After transplantation, the number of drug-induced rotations decreased markedly, and the mean SUR of 4-[ 18 F]-ADAM and the level of SERT immunoreactivity (SERT-ir) in striatum were partially restored. The mean SUR level was restored to 71% compared to that for the contralateral intact side, which together with the abundant survival of tyrosine hydroxylase (TH) neurons accounted for functional recovery at the fourth week postgraft. In regard to the extent of donor-derived cells, we found the neurons of the xenografts from E27 transgenic pigs harboring red fluorescent protein (RFP) localized with TH-ir cells and SERT-ir in the grafted area. Thus, transplanted E27 porcine mesencephalic tissue may restore dopaminergic and serotonergic systems in the parkinsonian rat. The 4-[ 18 F]-ADAM/animal PET can be used to detect serotonergic neuron loss in PD and monitor the efficacy of therapy.